The Career Coaching Handbook : Second edition - Yates, Julia, ....- (Oxon : Routledge, 2022)
Uniquely combining the latest research into careers with the most up to date coaching approaches, Julia Yates shows how to effectively apply coaching techniques to the world of career support. Demonstrating how coaching research explains practice and how practice benefits from research, The Career Coaching Handbook is accessibly written with a solid evidence-based foundation. Presented in three parts, the book covers developments in theory and research and applies this knowledge to the real world. Part 1, Theories of Career, looks at 21st century career paths, job satisfaction and career changes - both planned and unplanned. Part 2, Career Coaching Approaches, looks at coaching strategies that are applicable to career coaching in particular. Part 3, Coaching into the World of Work, covers specific real-world situations where coaching is beneficial, from job search strategies to CV and interview coaching. Evidence and research is used throughout to demonstrate the most effective strategies for coaching. The Career Coaching Handbook provides an essential introduction for students or practitioners who are interested in developing their own practice, finding new and improved ways to do things and understanding the theories that underpin effective career coaching practice.
Keywords: Career coaching